Hydrothermal treatment of Chlorella sp.: Influence on biochemical methane potential, microbial function and biochemical metabolism. (October 2019) - Wu, Houkai; Li, Jiaming; Yang, Hao; Liao, Qiang; Fu, Qian; Liu, Zhidan
Graphical abstract: Highlights: Hydrothermal severity impacted algae cell disruption and biomethane potential. Hydrothermal treatment facilitated hydrolysis and acidogenesis during digestion. A highest biomethane potential of 485 mLCH4 /gVS at the weakest severity. More fermentation inhibitors obtained at stronger hydrothermal severity. Microbial function and biochemical metabolism supported biogas production. Abstract: This study focused on the effect of hydrothermal treatment (HTT) on biochemical methane potential (BMP) of Chlorella sp. The BMP was in the range of 119.16–485.90 mLCH4 /gVS, and increased by 80.31%–210.16% after HTT, while reduced 23.94% at hydrothermal treatment severity (HTS) 5.21. The cell wall was more greatly disrupted with increasing HTS, accompanied with the increase of volatile fatty acids (VFAs) and fermentation inhibitors (5-HMF and more complex chemical compositions) recoveries. The reducing sugar yields were 0.94–3.65% and obtained its maximum at a retention time of 30 min. Illumina MiSeq sequencing clarified that, the phylum Chloroflexi with functions of hydrolysis and acidogenesis, decreased with increasing HTS. The family Methanosaetaceae belonging to acetoclastic methanogens, had an unexpected decrease at HTS 5.21. As the response, VFAs concentration was less than 1 g/L after biochemical metabolism, while high concentrations of VFAs and inhibitors at HTS 5.21 led to the poor performance.